Apocalyptic Environment Ecocritical of Qizink La Aziva’s Kelomang - Subagiyo, Ghulamin Khalim; Yuniawan, Tommy (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
So far, literature studies tend to be repetitive and normative. Whereas in analyzing literary works, it is important to note that a text has an impact and implication in life. The Kelomang novel written by Qizink La Aziva was chosen because it is one of the novel texts that does not only make the environment the setting, but also makes the environment a part of the story. The story in the Kelomang novel is characterized by apocalyptic. This study aims to find the apocalyptic environment in the Kelomang by Qizink La Aziva. This research is a qualitative research. This study uses an ecocritical approach to apocalyptic literature. The data source of this research is the text of the Kelomang by Qizink La Aziva published by PT Gramedia Pustaka Utama in Jakarta in 2016. The data in this study is a text fragment of the Kelomang by Qizink La Aziva which allegedly contains apocalyptic environmental ecocritics. The research results are as follows. 1) It is found that environmental changes that have occurred are garbage pollution, clean water crisis, vandalism, road damage, and damage due to mining activities. 2) Efforts to prevent environmental damage were found, such as cleaning up garbage in the yard of regional government offices and squares, as well as preventive preparations for rejecting sand mining. 3) There is human awareness of part of the environment carried out by Yanto and Citra. 4) There was an awareness of rejection of the temptation to impose their will on the environment, such as the repressive efforts of residents to reject the plan to mine sea sand by means of demonstrations and reject the presence of sand mining ships, and not to accept bribes made by businessmen and government officials to approve sea sand mining.